Acid‐catalyzed Disulfide‐mediated Reversible Polymerization for Recyclable Dynamic Covalent Materials - Wang, Bang‐Sen; Zhang, Qi; Wang, Zhi‐Qiang; Shi, Chen‐Yu; Gong, Xue‐Qing; Tian, He; Qu, Da‐Hui (Angewandte Chemie International Edition, 2023)
Poly(1,2‐dithiolane)s are a family of intrinsically recyclable polymers due to their dynamic covalent disulfide linkages. Despite the common use of thiolate‐initiated anionic ring‐opening polymerization (ROP) under basic condition, cationic ROP is still not exploited. Here we report that disulfide bond can act as a proton acceptor, being protonated by acids to form sulfonium cations, which can efficiently initiate the ROP of 1,2‐dithiolanes and result in high‐molecular‐weight (over 1000 kDa) poly(disulfide)s. The reaction can be triggered by adding catalytic amounts of acids and non‐coordinating anion salts, and completed in few minutes at room temperature. The acidic conditions allow the applicability for acidic monomers. Importantly, the reaction condition can be under open air without inert protection, enabling the nearly quantitative chemical recycling from bulk materials to original monomers. Acid can catalyze the reversible polymerization of cyclic disulfides, enabling a robust methodology that produces long poly(disulfide)s within a few minutes under open‐air condition. High‐yield chemical recycling from materials to monomers is achieved at gram scale, showing the capability of intrinsic dynamic polymers toward sustainable materials.